DYNAMICS OF IMMUNOLOGICAL INDICES IN WOUND HEALING ACCOMPANIED BY DIFFERENT TYPES REACTIVITY OF THE ORGANISM - Yarov, Yu.Yu.; Silenko, Yu.I.; Yeroshenko, G.A. (World of Medicine and Biology, 2021)
The dynamics of pro- and anti-inflammatory cytokines, circulating immune complexes of different sizes after surgical treatment of spontaneous periodontitis accompanied by normo-, hyper- and hyporeactivity of the organism was studied. It has been revealed that adequate time- and level-balanced changes in the studied indicators form a normoreactive response with synchronization of necrotic and reparative processes. In cases of hyperreactivity of the organism changes of immunological parameters boost strengthening of necrotic and delay of reparative processes during wound healing; in cases of hyporeactivity - changes in pro- and anti-inflammatory cytokines and circulating immune complexes of different sizes contribute to the slowing of necrotic processes, which also leads to delaying of wound healing. The revealed varying dynamics of indicators depending on the condition of reactivity of the organism preconditions necessity of their directed medical correction with reduction of indicators to those of normoreaction.
Keywords: reactivity of the organism; spontaneous periodontitis; wound healing; cytokines; circulating immune complexes